Foot and Ankle Reconstruction Using Retrograde Lateral Supramalleolar Flap - Nguyen, Thach Ngoc; Mai, Tuong Trong; Vo, Khanh Hoa; Nguyen, An Van; Nguyen, An Nguyen; Cao, Thi (Indian Journal of Plastic Surgery, 2024)
Background Treatment of soft-tissue defects in the foot and ankle is a challenge. The use of a retrograde lateral supramalleolar flap is a promising technique for reconstruction. This study aims to assess the efficacy and outcomes of the technique.Materials and Methods A prospective observational study was conducted from December 2017 to December 2022. Patients with soft-tissue defects in the foot and ankle underwent reconstruction using the retrograde lateral supramalleolar flap. Data on demographics, injury details, flap dimensions, complications, and outcomes were recorded and analyzed.Results Forty-six flaps were used in the study. The average flap length was 17.47 cm. The maximum size of the flaps was 104 cm2 with an average of 48.43 cm2. Venous congestion occurred in nine flaps, leading to partial necrosis in four cases. The overall success rate was 91.3%.Conclusion The retrograde lateral supramalleolar flap is effective in covering soft-tissue defects in the foot and ankle.
Keywords: retrograde lateral supramalleolar flap; foot and ankle reconstruction; soft-tissue defects; reconstructive surgical procedures